P-099 The effect of sperm DNA quality on blastocyst and euploid rates. (30th June 2022) - Exeter, H; Odia, R; Cawood, S; Haddock, L; Lewis, S; Srividya, S; Serhal, P; Saab, W
Abstract: Study question: Do sperm DNA quality measurements influence the blastocyst rate and/or euploid rates? Summary answer: Sperm DNA fragmentation has a negative influence on the rate of blastulation. It does not impact on euploidy rates assessed by pre-implantation genetic testing (PGT-A). What is known already: Some studies show that sperm DNA has no influence on embryo development and that its negative influence begins following implantation. Other studies show that every step of the fertility process from fertilization onwards is impacted by the male gamete as well as the female gamete. To date, data has been confounded by different sperm DNA tests and different clinical practices and parameters measured. Study design, size, duration: This was a retrospective study using the sensitive Comet assay to analyse whether it's three sperm DNA fragmentation scores influence embryo development or euploidy. Participants/materials, setting, methods: Data from 110 cycles of intracytoplasmic sperm injection (ICSI) where the blastocyst rate (number of blastocysts/number of mature oocytes injected) was obtained from the patient database of a UK single centre. Inclusion criteria: Only outcomes from the first assisted reproductive cycle after a Comet assay had been performed were included. Included cycles were within one year of the test. Main results and the role of chance: Blastocysts were ranked in 4 groups- 0.25-0.49, 0.5-0.74, 0.75-1.00. Three Comet scores were analysed: Average Comet Score (damage across the semen sample; ACS), Low Comet Score (proportion of sperm with good DNA; LCS) and High Comet Score ( proportion of sperm with high DNA damage; HCS). Clinical thresholds were calculated by comparison with fertile donor sperm. High ACS and LCS and low HCS were all associated with higher blastocyst rates (ANOVA, p = 0.013; Kruskal Wallis, p = 0.027, Post Hoc pairwise comparisons between blastocyst groups (p = 0.016-0.024). No relationship was found between euploid rate (number of euploid embryos/total embryo number) and sperm DNA damage p = 0.761). Limitations, reasons for caution: Retrospective design requiring more data to clarify these associations coupled with the lack of randomisation and low power analysis. Wider implications of the findings: This study reports the negative impact of sperm DNA fragmentation on blastocyst formation rates. Male partner diagnostic assessments such as sperm DNA quality testing are useful adjuncts to semen analysis. Further research to determine if there is a relationship between sperm DNA damage and euploid embryo outcomes is ongoing. Trial registration number: IRB-001C06-01-22